Treasure in the Light of the Holy Quran - Thamer, Hasna Hamid (Journal of Islamic Sciences, 2025)
The subject of this research addresses a very important issue, which is knowing the terms of treasure in the light of the Holy Quran to help contemplate the verses and live with them. The researcher has taken the descriptive, inductive, and deductive approach to the verses of treasure in the light of the Holy Quran. This research shows the moral and corporeal values of treasure in the Holy Quran and explains the effect of treasure on the individual and society. The researcher has discovered the following: ● The best types of treasure are those that come with the meaning of knowledge that elevates a person to ranks that he will not reach except through knowledge. ● Treasure has many meanings in the Holy Quran, some of which are material and some of which are moral. ●Through my research and study, I have concluded that if a person does not dispose of treasures as God has commanded, they will lead to negative effects on the individual and society. ● The amount of money that matches the concept of treasure.